Structural Optimization of Automotive Chassis - Nakkeeran, S. (International Journal of Psychosocial Rehabilitation, 2019)
Improvements in structural components design are often achieved on a terminal and error basis guided by the designer known how. Despite the designer experience must remain a fundamental aspect in design, such an approach is like to allow only marginal product enhancements. A different turn of mind that could boost structural design is needed and could be given by structural optimization methods linked with finite elements analyses. These methods are here briefly introduced, and some applications are presented and discussed with the aim of showing their potential. A particular focus is given to weight reduction in automotive chassis design applications following the experience matured at milechil Lab.